Walking a Tightrope: Creating Value Through Interorganizational Relationships - Barringer, Bruce R.; Harrison, Jeffrey S. (Journal of Management, 2000)
This paper provides an overview of the literature on interorganizational relationships. Although the literature on interorganizational relationships is extensive, a pervasive theme that is either explicit or implicit in the majority of the articles is the simple notion of whether interorganizational relationships make sense and whether the advantages outweigh the disadvantages. This article reviews six widely used theoretical paradigms that explain interorganizational relationship formation, including transaction costs economics, resource dependency, strategic choice, stakeholder theory, organizational learning, and institutional theory. Although each paradigm alone is insufficient to capture the complexities of interorganizational relationship formation, the fact that interorganizational relationships can be justified from such diverse theoretical backgrounds is impressive. The paper also reviews the six forms of interorganizational relationships most commonly pursued in practice and discussed in the literature, including joint ventures, networks, consortia, alliances, trade associations, and interlocking directorates. Through these discussions, we elaborate on the potential advantages and disadvantages of participation in interorganizational relationships.